The new journal for conservationists worldwide - Paudel, Prakash Kumar; Shrestha, Uttam Babu; Ameixa, Olga MCC; Bontzorlos, Vasileios (Conservation Science, 2014)
DOI: http://dx.doi.org/10.3126/cs.v1i1.9586 Conservation Science 2013 1(1), 53-54